What Happens When There Is Presumptive 50/50 Parenting Time? An Evaluation of Arizona's New Child Custody Statute. Issue 5 (4th July 2018) - Fabricius, William V.; Aaron, Michael; Akins, Faren R.; Assini, John J.; McElroy, Tracy
ABSTRACT: The current study presents the findings of an evaluation of Arizona's 2013 revisions to the child custody statutes that directed courts to "maximize" the child's parenting time with both parents. A state-wide survey of the four family law professions (i.e., conciliation court staff, judges, mental health providers, and attorneys) assessed their perceptions of the law 4 years after implementation. We averaged the ratings across the four professions to obtain a comprehensive perspective that gave equal weight to each profession. Results revealed that the law functions as a rebuttable presumption of equal parenting time; that it is evaluated positively overall and in terms of children's best interests; that it is has a neutral impact on legal and interparental conflict; and that it has led to small increases in allegations of domestic violence, child abuse, and substance abuse.